Effectiveness of Ammonium Polymer in Improving Floating Treatment Wetland to Reduce Cod From Palm Oil Mill Effluent - Hakim, Lukman; Rahayu, Aster; Jamilatun, Siti (Sains Natural: Journal of Biology and Chemistry, 2025)
Palm oil mill effluent (POME) is a liquid waste from the palm oil industry. This waste contains high levels of organic pollutants and can contribute to environmental pollution. Current technologies effectively degrade these pollutants but are often not environmentally friendly and expensive. Phytoremediation combined with an adsorption system using ammonium polymers is expected to address these challenges. Vetiver grass (Chrysopogon zizanioides) and ammonium polymers have been separately tested and proven capable of degrading pollutants in wastewater. The study began by modifying the planting medium for vetiver grass with gravel:polymer:soil ratio of 3:5:2. The modified net pot was then placed in a floating treatment wetland reactor for POME treatment over a remediation period of 7 days. For comparison, a control experiment was conducted using plants without polymers in the planting medium. The results showed a COD degradation of approximately 75% in POME after treatment. The reduction in COD continued to improve with increasing remediation time, reaching its peak on the seventh day. The modified planting medium also influenced plant growth, as the polymer adsorbed some phosphate and nitrate.